Characteristics of family farming in two fruit producer associations in Arbeláez, Cundinamarca, Colombia - Pardo-Romero, Alejandra (2022)
The need for a sustainable and equitable agriculture is a requirement that increases its demand day by day, this is a challenge that undoubtedly must be faced from the local level and based on the importance of local producers and the impact that family farming can have on the growing challenge of achieving food security and reducing rural gaps. The information on the characterization of family farming in Colombia is scarce; therefore, the objective of this research was to determine the relationship between the characteristics of family farming present in the fruit producers' associations ASPROFRUTAS and ASOCMA in the municipality of Arbeláez, Cundinamarca, Colombia. A review of documents with information associated with basic concepts of family farming was carried out, as well as the realization of these focus groups, where the participants were given surveys for their development. In the research it was found that the occupation of the family labor force, the size of the plot that allows satisfying the basic needs of the family, the destination of the final production with emphasis on self-consumption and the place of residence of the producer located near or within the area where he works, are the most relevant characteristics for family agriculture, which allows establishing that the associations ASOCMA and ASPROFRUTAS BERLÍN belong to the category of family agriculture.